Food polyphenols interaction with bitter taste receptors - Gonçalves, Maria Leonor Pestana (2020)
Polyphenols are widspread in plant-based foodstufs contributing directly to their taste properties (astringency and bitter taste).Bitteness is perceived by avtivation of bitter aste receptors (TAS2Rs). Some polyphenols have been already identified as agonists for TAS2R5, TAS2R7 ND TAS2R39. The aim of this study was to express and isolate TAS2R5, TAS2R7 AN TAS2R39 on S. cerevisiae for further structure-activation studies. For this purpose, these TAS2Rs were expressed using a GFP-fusion yeast system. The transformants and the induction culture conditions (time, temperature, and addition of a chemical chaperone) were screened by whole-cell GFP fluorscence, immunoblotting and fluorscence microscopy. An increase of expression of TAS2Rs was observed whwn were induced with 2% of galactose at 20C (TARS2R5), 26C (TAS2R7), and with 2.5% of DMSO at 26C (TAS2R39) for 22 hours. Isolation of TAS2R has been proven difficult due to cell lysis inefficiency and protein degradation. This study allowed to get the insights on the best protein expression conditions for these TAS2Rs. The future work is focused on improving the isolation of these membrane proteins and finding alternative approaches. Ongoing work is developing two approaches based on a baculovirus expression ector system and on expression on an engineered GPCR-based signalling strain S. cerevisiae.